Application of intelligent water dissection technology in sculpting the lateral surface of putamen during insular glioma surgery - WU Dong⁃dong; SHU Xu⁃jun; ZHAO Kai; CONG Xiao⁃jun; ZHOU Xing⁃yu; XIA Ying; SUN Guo⁃chen (Chinese Journal of Contemporary Neurology and Neurosurgery)
Background In insular glioma surgery, accurately localizing the lateral surface of putamen remains challenging. This study aimed to explore a water dissection⁃based technique for sculpting the lateral surface of putamen during insular glioma surgery. Methods and Results Total 17 patients with insular glioma hospitalized in the Department of Neurosurgery, The First Medical Center of Chinese PLA General Hospital from January 2020 to December 2024, all of the tumor were not involved in the putamen and the tumor was resected by trans⁃frontal isthmus approach. A self⁃ constructed low⁃pressure water flow system was used to separate the Sanai⁃Berger zoneⅠ(2 cases), Ⅰ + Ⅳ(6 cases), andⅠ + Ⅳ + Ⅲ + Ⅱ(9 cases). The bottom of the tumor was easily separated from the lateral surface of the putamen, and the lenticulostriate artery exposed on the lateral surface of the putamen was not damaged during the operation, and the separation process was smooth. Within 24 h after surgery, MRI showed the separation of the lateral surface of the putamen from the tumor was appropriate, the lateral surface of the putamen was sharp and regular, and the tumors were nearly completely removed, and the separation effect was good. No complications related to water dissection occurred. At 3 months follow⁃up, aphasia quotient (AQ) was > 93.80, the operative related side muscle strength was > 4+, and Karnofsky Performance Status (KPS) median score was 90 (90, 100). Conclusions For low⁃grade insular gliomas without putamen involvement characterized by "Jing⁃Wei River sign", water dissection effectively delineates the tumor⁃putamen surface, reduces surgical difficulty, shortens the learning curve, and enhances safety and efficiency.